If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(4-3x)=4(11-5x)
We move all terms to the left:
6(4-3x)-(4(11-5x))=0
We add all the numbers together, and all the variables
6(-3x+4)-(4(-5x+11))=0
We multiply parentheses
-18x-(4(-5x+11))+24=0
We calculate terms in parentheses: -(4(-5x+11)), so:We get rid of parentheses
4(-5x+11)
We multiply parentheses
-20x+44
Back to the equation:
-(-20x+44)
-18x+20x-44+24=0
We add all the numbers together, and all the variables
2x-20=0
We move all terms containing x to the left, all other terms to the right
2x=20
x=20/2
x=10
| v/6+1=2 | | 12y+7=8y+35 | | 4(5x-6)=-284 | | (9x+17)=(3x-4)=(6x-31) | | 15=3/5y | | 19=x/4+15 | | 7(x+4)=2/3x+6 | | 6y+6=-2 | | 2x=5+1 | | x/3+17=36 | | 4u-11=41 | | 6=-5+v | | 5w-2=+1 | | x+37=49 | | x°+100= 180° | | x°+100° = 180° | | -3x²=23 | | -4(-5-x)=1/3(x=16) | | 2y^2+11y+5-((y+5)^2)=0 | | (x/4)+(x/2)+x+x+3=300 | | v6+1=2 | | 2y^2+11y+5=(y+5)^2 | | x+.2x=90 | | 6g–15=-3 | | 2r–3=1 | | -7r=-4r-6 | | -19+12q=5 | | -47=-u/3 | | -45=-w/5 | | 3-9x=7x(x+5) | | 3(12x+1)=471 | | 41=w/5+17 |